Effective enhancement of the immunomodulatory capacity of canine adipose-derived mesenchymal stromal cells on colitis by priming with colon tissue from mice with colitis - Yasumura, Yuyo; Teshima, Takahiro; Nagashima, Tomokazu; Michishita, Masaki; Taira, Yoshiaki; Suzuki, Ryohei; Matsumoto, Hirotaka (Frontiers in Veterinary Science, 2024)
The therapeutic efficacy of mesenchymal stromal cells (MSCs) in inflammatory bowel disease is not completely known and is not consistent. Priming with inflammatory cytokines has been proposed to adapt MSCs to an inflammatory environment to have them ready to counteract it, but may have undesirable effects on MSCs, such as increased immunogenicity. In this study, we hypothesized that priming MSCs with inflamed intestinal tissue would more effectively enhance their therapeutic effect on intestinal inflammation. The capacity of canine adipose-derived MSCs (cADSCs) primed with colon tissue homogenates from mice with experimentally induced colitis or a combination of tumor necrosis factor-α and interferon-γ to inhibit T-cell proliferation was analyzed, along with their own apoptosis, proliferation, cell surface marker expression, and transcriptome. In addition, colitis mice were treated with the primed cADSCs to assess colitis severity and immune cell profile. Priming with cytokines induced apoptosis, decreased cell proliferation, and major histocompatibility complex-II gene expression in cADSCs, but these adverse effects were mild or absent with colitis-tissue priming. cADSCs primed with colitis tissue reduced the severity of colitis via the induction of M2 macrophages and T-regulatory cells and suppression of T-helper (Th)1/Th17-cell responses, and their effects were comparable to those of cytokine-primed cells. Our results emphasize the importance of the activation of MSCs by the appropriate microenvironment to maximize their therapeutic effect.